Circulating microRNA-126 increases after different forms of endurance exercise in healthy adults. (April 2014) - Uhlemann, Madlen; Möbius-Winkler, Sven; Fikenzer, Sven; Adam, Jennifer; Redlich, Maren; Möhlenkamp, Stefan; Hilberg, Thomas; Schuler, Gerhard C; Adams, Volker
Background: MicroRNAs (miRNAs) are small non-coding molecules regulating gene expression. Recently circulating miRNAs could be detected in the plasma, serving as novel biomarkers. Different forms of exercise mobilize progenitor cells from the bone marrow, helping in tissue repair. Data of different forms of exercise on endothelial cell damage are lacking. The aim of the study was to evaluate the impact of different exercise modalities on the plasma concentration of miRNA-126, as a marker for endothelial damage. Methods: The plasma concentration of miRNA-126 and miRNA-133 (marker for muscle damage) was assessed by qRT-PCR analysis in plasma samples from healthy individuals performing one of the following exercise tests: (1) maximal symptom-limited exercise test, (2) bicycling for 4 h, (3) running a marathon, and (4) resistance exercise. Results: A maximal symptom-limited exercise test resulted in a significant increase of circulating miRNA-126 at maximum power (2.1-fold versus begin), whereas the concentration of miRNA-133 remained unchanged. In line, four hours of cycling increased plasma concentration of miRNA-126 with a maximum 30 minutes after begin (4.6-fold versus begin) without an impact on miRNA-133 concentration. Finishing a marathon race resulted in an increase of miRNA-126 and miRNA-133. In contrast, eccentric resistance training led to an isolated increase of miRNA-133 level (2.1-fold versus begin) with unchanged miRNA-126. Conclusion: Different endurance exercise protocols lead to damage of the endothelial cell layer as evident by an increase in miRNA-126. On the other hand, resistance exercise has no impact on the endothelial cells, but leads to a destruction of muscular cells.